Effects of short term laboratory infestation of dried cassava variety TME-7 by prostephanus truncatus (horn) (coleoptera: bostrichidae) (2009)
Researches have shown that dried cassava varieties are relatively susceptible to Prostephanus truncatus (Horn) infestation. Laboratory studies were conducted to determine weight loss and nutritional status of dried cassava chips (TME-7) and P. truncatus emergence rate over an infestation period of 8 weeks. TME-7 mean weight loss (±SD) rose to 11.30% ± 4.01 (22.67%) with P. truncatus mean emergence rate (± SD) of 18.50 ± 8.25; 16.33 ± 6.85 and 9.93 ± 3.30 for larvae, pupae and adults respectively. Nutrition proximate analysis conducted on infested TME-7 revealed the dried cassava nutritional status as follows: protein content was 1.30%; fat content recorded was 0.99%, while moisture content was put at 5.50%. Other parameters analyzed were ash content which was 1.81%, and lastly, crude fiber and carbohydrate was 29.03%. The dried cassava variety supports P. truncatus breeding, with appreciable damage to the crop. Breeding and damage have been implicated in the reduction of nutritional and market values of the dried cassava.